2011
DOI: 10.1242/jcs.086470
|View full text |Cite
|
Sign up to set email alerts
|

KLP6: a newly identified kinesin that regulates the morphology and transport of mitochondria in neuronal cells

Abstract: Mitochondria utilize diverse cytoskeleton-based mechanisms to control their functions and morphology. Here, we report a role for kinesin-like protein KLP6, a newly identified member of the kinesin family, in mitochondrial morphology and dynamics. An RNA interference screen using Caenorhabditis elegans led us to identify a C. elegans KLP-6 involved in maintaining mitochondrial morphology. We cloned a cDNA coding for a rat homolog of C. elegans KLP-6, which is an uncharacterized kinesin in vertebrates. A rat KLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 48 publications
3
45
0
1
Order By: Relevance
“…This family of motors is, however, critical for the transport of synaptic vesicle precursors (Hall and Hedgecock 1991;Yonekawa et al 1998;Pack-Chung et al 2007;Barkus et al 2008). A distantly related member of the Kinesin-3 family, kinesin-like protein 6 (KLP6), was found to alter mitochondrial shape in Caenorhabditis elegans and mitochondrial motility in HeLa cells and a neural cell line (Tanaka et al 2011) when mutated or knocked down with RNA interfer-ence (RNAi). Whereas loss of the conventional kinesin heavy chain prevented mitochondria from entering axons at all, mutant forms of KLP6 and Kif1Ba altered the velocity of axonal mitochondria (Tanaka et al 2011).…”
Section: Other Mechanisms For Mitochondrial Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…This family of motors is, however, critical for the transport of synaptic vesicle precursors (Hall and Hedgecock 1991;Yonekawa et al 1998;Pack-Chung et al 2007;Barkus et al 2008). A distantly related member of the Kinesin-3 family, kinesin-like protein 6 (KLP6), was found to alter mitochondrial shape in Caenorhabditis elegans and mitochondrial motility in HeLa cells and a neural cell line (Tanaka et al 2011) when mutated or knocked down with RNA interfer-ence (RNAi). Whereas loss of the conventional kinesin heavy chain prevented mitochondria from entering axons at all, mutant forms of KLP6 and Kif1Ba altered the velocity of axonal mitochondria (Tanaka et al 2011).…”
Section: Other Mechanisms For Mitochondrial Movementmentioning
confidence: 99%
“…A distantly related member of the Kinesin-3 family, kinesin-like protein 6 (KLP6), was found to alter mitochondrial shape in Caenorhabditis elegans and mitochondrial motility in HeLa cells and a neural cell line (Tanaka et al 2011) when mutated or knocked down with RNA interfer-ence (RNAi). Whereas loss of the conventional kinesin heavy chain prevented mitochondria from entering axons at all, mutant forms of KLP6 and Kif1Ba altered the velocity of axonal mitochondria (Tanaka et al 2011). Both of these Kinesin-3 motors have been shown to bind to a candidate adaptor protein, the kinesin binding protein (KBP).…”
Section: Other Mechanisms For Mitochondrial Movementmentioning
confidence: 99%
“…Long-distance movement of mitochondria in axons is driven by kinesin and dynein motors along microtubules that are arranged with their plus ends toward synaptic terminals (Figs 1, 2). Function inhibition and biochemical studies indicate that kinesin-1 is the primary anterograde mitochondrial motor (Barkus et al, 2008;Pilling et al, 2006;Vale et al, 1985), but there is evidence from studies of tissue culture cells that the kinesin-3 motors Kif1b and Klp6 also can transport mitochondria and thus might do so in axons (Nangaku et al, 1994;Tanaka et al, 2011). Similar approaches indicate that cytoplasmic dynein is the primary retrograde mitochondrial motor (Pilling et al, 2006;Schnapp and Reese, 1989).…”
Section: Box 1 Mitochondria Overviewmentioning
confidence: 99%
“…In vivo and in vitro studies have identified several kinesin family members, including KIF5A/B/C, KIF1B␣, and KLP6, that are involved in mitochondrial anterograde transport (3)(4)(5)(6)(7). In addition to the motor proteins, intracellular signaling pathways that regulate mitochondrial movement have also been investigated.…”
mentioning
confidence: 99%